Plasmodium vivax spleen-dependent protein 1 and its role in extracellular vesicles-mediated intrasplenic infections - Ayllon-Hermida, Alberto; Nicolau-Fernandez, Marc; Larrinaga, Ane M.; Aparici-Herraiz, Iris; Tintó-Font, Elisabet; Llorà-Batlle, Oriol; Orban, Agnes; Yasnot, María Fernanda; Graupera, Mariona; Esteller, Manel; Popovici, Jean; Cortés, Alfred; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Recent studies indicate that the human spleen contains over 95% of the total parasite biomass during chronic asymptomatic infections caused by Plasmodium vivax. Previous studies have demonstrated that extracellular vesicles (EVs) secreted from infected reticulocytes facilitate binding to human spleen fibroblasts (hSFs) and identified parasite genes whose expression was dependent on an intact spleen. Here, we characterize the P. vivax spleen-dependent hypothetical gene (PVX_114580). Using CRISPR/Cas9, PVX_114580 was integrated into P. falciparum 3D7 genome and expressed during asexual stages. Immunofluorescence analysis demonstrated that the protein, which we named P. vivax Spleen-Dependent Protein 1 (PvSDP1), was located at the surface of infected red blood cells in the transgenic line and this localization was later confirmed in natural infections. Plasma-derived EVs from P. vivax-infected individuals (PvEVs) significantly increased cytoadherence of 3D7_PvSDP1 transgenic line to hSFs and this binding was inhibited by anti-PvSDP1 antibodies. Single-cell RNAseq of PvEVs-treated hSFs revealed increased expression of adhesion-related genes. These findings demonstrate the importance of parasite spleen-dependent genes and EVs from natural infections in the formation of intrasplenic niches in P. vivax, a major challenge for malaria elimination.